PENGARUH INTEGRITAS, OBJEKTIVITAS, DAN KOMPETENSI AUDITOR INTERNAL TERHADAP EFEKTIVITAS AUDIT INTERNAL DENGAN GAYA KEPEMIMPINAN DEMOKRASI SEBAGAI VARIABEL MODERASI PADA INSPEKTORAT JENDERAL KEMENTERIAN DALAM NEGERI - Prihartono Prihartono; Theresia Theresia; Sekar Mayangsari (Jurnal Magister Akuntansi Trisakti, 2018)
This study aims to examine the effects of integrity, objectivity, and competence of internal auditor to the effectiveness of internal audit with the democratic leadership style as the moderating variable. This study uses primary data and obtained using a questionnaire instrument. The sample used in the study were 93 respondents who were the auditors of Inspectorate General Ministry of Internal Affairs. Statistical and analysis process using the moderated regression analysis to test whether the independent variables have a positive influence on the dependent variable and strengthen by the moderating variable. This study finds that integrity does not affect the effectiveness of the internal audit, while the democratic leadership style, objectivity, and competence have a positive impact on the effectiveness of the internal audit. The democracy leadership style is not proven to strengthen the integrity, objectivity, and competence effect toward the effectiveness of the internal audit.